2015
DOI: 10.4269/ajtmh.14-0098
|View full text |Cite
|
Sign up to set email alerts
|

Possible Vertical Transmission of Bartonella bacilliformis in Peru

Abstract: Abstract. A 22-day-old male was admitted with a 2-day history of irritability, dyspnea, jaundice, fever, and gastrointestinal bleeding. A thin blood smear was performed, which showed the presence of intraerythrocyte bacteria identified as Bartonella bacilliformis, and subsequently, the child was diagnosed with Carrion's disease. The diagnosis was confirmed by specific polymerase chain reaction. The child was born in a non-endemic B. bacilliformis area and had not traveled to such an area before hospitalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In contrast to those studies, no congenital infections were recognized in bank voles Myodes glareolus in the UK [ 12 ]. Several cases of human congenital bartonellosis have been reported and attributed to different species of Bartonella [ 30 , 31 ], including the case of a 22-day-old boy from Peru [ 32 ]. All of the above findings indicate that further studies on vertical transmission of these vector-borne bacteria are still needed to enable a comprehensive epidemiological assessment of the risk of infection by this route.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to those studies, no congenital infections were recognized in bank voles Myodes glareolus in the UK [ 12 ]. Several cases of human congenital bartonellosis have been reported and attributed to different species of Bartonella [ 30 , 31 ], including the case of a 22-day-old boy from Peru [ 32 ]. All of the above findings indicate that further studies on vertical transmission of these vector-borne bacteria are still needed to enable a comprehensive epidemiological assessment of the risk of infection by this route.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, in the first third of the 20th century, Monge and Strong in 1912 and 1913, respectively, and both Malpartida and Colaretta in 1937 also reported different cases of vertical transmission (3,48,227,230). More recently, several authors have also reported different cases (15,48,(231)(232)(233), with the most evident description being of a B. bacilliformis-positive culture obtained from the blood of a preterm child collected 90 min after birth (231) ( Table 4).…”
Section: Vertical Transmissionmentioning
confidence: 99%
“…A 22-day-old presented with Oroya fever confirmed on blood by PCR, where the mother retrospectively had a febrile illness in the third trimester and was identified with vascular cutaneous lesion consistent with verruga peruana. 175 Other cases include a 19-day-old with Oroya fever, where the mother was also blood smear positive and a pre-term newborn of 90 min with a confirmed bartonellosis on blood culture in a mother with verrucous lesions. There is an overall paucity of reporting of Carrion’s disease, especially in pregnancy.…”
Section: Triatomine Bug- and Fly-borne Diseases In Pregnancymentioning
confidence: 99%